Etika Kehumasan dan Kedudukannya dalam Manajemen Pendidikan - Azyan Zafirah Sulhair; Dzulfiana Parwati; Sulis Maryati (CV. ITTC INDONESIA, 2026)
This article aims to analyze the fundamental concept of public relations ethics and its position within educational management. The method employed is a literature review involving an examination of laws and regulations, public relations governance guidelines, professional codes of ethics for public relations practitioners, and relevant Indonesian journal articles concerning communication ethics, educational public relations, public services, and educational institution governance. The findings indicate that public relations ethics serves as a moral and professional foundation that guides educational institutions in delivering information honestly, transparently, proportionally, and accountably while protecting students’ privacy. Within educational management, public relations ethics functions as a guiding principle in the planning, organizing, implementation, supervision, and evaluation of institutional communication. In this capacity, public relations ethics not only serves to maintain the institution’s image but also strengthens public trust, prevents information-related conflicts, improves service quality, and supports professional, participatory, and accountable educational governance.